Xuefu Zhuyu decoction for nonalcoholic fatty liver disease: A protocol for systematic review and meta-analysis. Issue 19 (14th May 2021) - Liu, Jiaxin; Dong, Bo; Yang, Lin; Huang, Wei; Tang, Songqi
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) includes nonalcoholic fatty liver (NAFL) and nonalcoholic steatohepatitis (NASH), which ranks only second to viral hepatitis and poses an increasingly serious challenge to global public health and economy. NAFLD has attracted more and more attention, but there is no drugs with exact curative effects are available. The commonly used drugs for the treatment of NAFLD in clinical practice are statins, such drugs, inevitably increase the burden on the live. Compared to statins, traditional Chinese medicines are believed to be "all natural" with fewer side effects, are associated with strong patient compliance. Accordingly, a great deal of clinical studies have shown that Xuefu Zhuyu decoction (XFZYD) can significantly improve the clinical symptoms and enhance the therapeutic effect. Meanwhile, a system review and meta-analysis are conducted by us to further clarify the effectiveness and safety of XFZYD for NAFLD. Methods: We will apply to database mainly range from the English literature searches Cochrane Library, PubMed, excerpt medica database, and Web of Science to the Chinese literature China national knowledge infrastructure, Chinese biomedical literature database, VIP, and Wanfang database, randomized controlled trials (RCTs) are enrolled to evaluate the effectiveness and safety of XFZYD in the treatment of NAFLD, the enrollment of RCTs is from the establishment of the database to February 01, 2021. Simultaneously we will retrieval clinical registration tests and grey literatures. The 2 researchers worked independently on literature selection, data extraction, and quality assessment. The dichotomous data is expressed in terms of relative risk, the continuous is represented by mean difference or standard mean difference, whether there is heterogeneity is the factor that determines the synthesis of data in fixed effect model or random effect model. Alanine aminotransferase (ALT) or Aspartic acid aminotransferase (AST) coupled with Glutamyltransferase (GGT) is considered as one of the main indicators of the NAFLD, while the pathology, imaging and diagnosis of metabolic syndrome are also auxiliary results. The last, meta-analysis was conducted by RevMan software version 5.3. Results: This study will provide evidence for treatment of NAFLD with XFZYD in terms of effectiveness and safety. Conclusion: This systematic review aims to confirm the efficacy and safety of XFZYD in the treatment of NAFLD. OSF registration number: DOI 10.17605/OSF.IO/7CWRK.